2000
DOI: 10.1161/01.res.86.3.293
|View full text |Cite
|
Sign up to set email alerts
|

The ε Subtype of Protein Kinase C Is Required for Cardiomyocyte Connexin-43 Phosphorylation

Abstract: Gap junctions (GJs), composed of connexins, are intercellular channels ensuring electric and metabolic coupling between cardiomyocytes. We have shown previously that an endogenous mitogenic and cardioprotective protein, fibroblast growth factor-2 (FGF-2), decreases cardiomyocyte GJ permeability by stimulating phosphorylation of connexin-43 (Cx43). Identifying the kinase(s) phosphorylating cardiac Cx43 may thus provide a way of modulating cardiac intercellular communication. Because FGF-2 activates receptors li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 45 publications
7
132
0
Order By: Relevance
“…From these results, which indicated that p-PKCε Ser729 was key to induced cardioprotection, it was found that p-PKCε Ser729 could phosphorylate cytoplasmic membrane proteins such as CX43 and that the phosphorylation of CX43 could decrease cardiomyocyte GJ permeability, prevent the spreading of injury between conjoined cells and finally enhance resistance to ischemic injury. 30 Phosphorylation by PKCε opens mitoKATP channels, preserving mitochondrial function and generating local ROS, 31 which can further activate PKCε in a positive feedback mechanism and confer cardioprotection. 19 A significant quantitative difference in PKCε and p-PKCε Ser729 was observed between the early and late phases of EP.…”
Section: Discussionmentioning
confidence: 99%
“…From these results, which indicated that p-PKCε Ser729 was key to induced cardioprotection, it was found that p-PKCε Ser729 could phosphorylate cytoplasmic membrane proteins such as CX43 and that the phosphorylation of CX43 could decrease cardiomyocyte GJ permeability, prevent the spreading of injury between conjoined cells and finally enhance resistance to ischemic injury. 30 Phosphorylation by PKCε opens mitoKATP channels, preserving mitochondrial function and generating local ROS, 31 which can further activate PKCε in a positive feedback mechanism and confer cardioprotection. 19 A significant quantitative difference in PKCε and p-PKCε Ser729 was observed between the early and late phases of EP.…”
Section: Discussionmentioning
confidence: 99%
“…PKCα and ε were found to associate with Cx43 in cardiomycytes (Bowling et al, 2001). Fibroblast growth factor-2, which decreases cardiomyocyte gap junctional permeability and increases Cx43 phosphorylation, increased colocalization of PKCε with Cx43 (Doble, Ping, & Kardami, 2000). Thus, it appears that several members of the conventional and novel PKC families influence gap junctional communication.…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 99%
“…Conversely, phosphorylation of Ser-365 by protein kinase A (PKA) promotes gap junction assembly and communication (Burghardt et al, 1995;Solan et al, 2007;TenBroek et al, 2001). Although several isozymes of protein kinase C (PKC) phosphorylate connexin-43 in diverse cell types and tissues, PKC is the only isoform that phosphorylates it at the ID (Bowling et al, 2001;Doble et al, 2000;Lampe et al, 2000;Lin et al, 2003;Saez et al, 1997). Consistent with this, PKC suppresses gap junction communication in the ischemic heart through phosphorylation of connexin-43 at Ser-368 (Ek-Vitorin et al, 2006;Hund et al, 2007;Hund et al, 2008).…”
Section: Phosphorylation Regulates the Permeability Of Connexonsmentioning
confidence: 88%